2010
DOI: 10.14742/ajet.1099
|View full text |Cite
|
Sign up to set email alerts
|

Effective practice with e-portfolios: How can the UK experience inform implementation?

Abstract: This paper introduces the background to the JISC work within the e-portfolio domain in the UK and presents an overview of past and current activities and the drivers for these developments. This is followed by a review of JISC's approach to drawing out the learning and implications for e-portfolio practice from this extensive collection of work and its dissemination. The analysis of twenty one recently funded projects involving the use of e-portfolios in the UK is introduced. The findings suggest that eportfol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 3 publications
1
58
0
3
Order By: Relevance
“…Our audits of student eportfolio work reinforce the opinion of various writers in the area of educational technology, that uses of forms of online infrastructure in teaching and learning are complex, and not one-dimensional or straightforward (e.g. Joyes, 2010;Gray et al, 2010).…”
Section: Resultssupporting
confidence: 65%
“…Our audits of student eportfolio work reinforce the opinion of various writers in the area of educational technology, that uses of forms of online infrastructure in teaching and learning are complex, and not one-dimensional or straightforward (e.g. Joyes, 2010;Gray et al, 2010).…”
Section: Resultssupporting
confidence: 65%
“…For example, a study of students in 38 Australian universities found that 84% of participants from a range of faculties agreed or strongly agreed that using ePortfolio software assisted them in evaluating and reflecting on their learning journey (Hallam et al, 2008). Similarly, students in the UK (Joyes, Gray, & Hartnell-Young, 2010) and USA have reported similar findings with regard to the strength of ePortfolios as a learning tool (Bartlett, 2006;Peters, Chevrier, LeBlanc, Fortin, & Malette, 2006;Ring & Foti, 2006). Support for the ePortfolio is reasonably strong and widespread.…”
Section: Use Of Portfolios and Eportfolios In Teacher Educationmentioning
confidence: 78%
“…Goldsmith (2007) described an ePortfolio as a flexible teaching and learning tool which allows both teachers and students to revisit learning and make clearer links to such learning (Chambers & Wickersham, 2007;Joyes, Gray, & Hartnell-Young, 2010;Reynolds & Patton, 2015;Yancey & Hunt, 2009). In an Aotearoa New Zealand context, Heinrich et al (2007) investigated ePortfolios as a 'life-long learning' tool at Massey University.…”
Section: Tertiary (Higher Education) Sectormentioning
confidence: 99%